Narsiso Federico celebrates his 93rd birthday in hospital. (Raton, New Mexico Raton Range, 1973)
Newspaper Article on the 93rd birthday of Narciso Federici.
Master list item #: 35
File location is in the Raton File Cabinet
Keywords: Federici, Narciso; Colfax General Hospital; Local History; Biography; Life and Customs; Birthday; Celebration; Raton, New Mexico; Springer, New Mexico; Boulder, Colorado; Cimarron, New Mexico; Santa Fe, New Mexico